2005
DOI: 10.1111/j.1365-3180.2005.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions in mixtures of broccoli and Chenopodium album grown at two UV‐B radiation levels under glasshouse conditions

Abstract: Ultraviolet-B radiation effects on intra-and interspecific competition in broccoli (Brassica oleracea) and Chenopodium album were studied using bivariate factorial experiments. A randomized block design was used in which three monoculture densities for each species [144 (low), 256 (medium), and 400 (high) plants m )2 ] and all binary combinations were grown in a glasshouse at two (4 and 7 kJ m )2 day )1 ) UV-B BE radiation levels for 4 weeks in 1999 and 5 weeks in 2000. Inverse yield-density relationships were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Jansen ; Furness et al . ). It is likely that these aboveground effects will also affect the root:shoot ratio.…”
Section: Whole‐plant Phenotype and Uv‐bmentioning
confidence: 97%
See 3 more Smart Citations
“…Jansen ; Furness et al . ). It is likely that these aboveground effects will also affect the root:shoot ratio.…”
Section: Whole‐plant Phenotype and Uv‐bmentioning
confidence: 97%
“…For example, UV‐B‐induced shifts in competitive interactions were found in a greenhouse study with broccoli ( Brassica oleracea ) and Chenopodium album (Furness et al . ). Broccoli gained in competitiveness relative to C. album in response to above ambient UV‐B exposure conditions.…”
Section: Uv‐b‐induced Morphogenesis and Plant–plant Interactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Some previous studies showed that weed species differed significantly in their susceptibility to UV-B radiation (Furness et al 1999;Furness and Upadhyaya 2002;Dai et al 2004). Increased UV-B radiation also changed the competition balance between wheat and wild oat (Li et al 1999;Furness et al 2005). However, little information is available on the growth response to increased UV-B radiation in most of the important weeds.…”
mentioning
confidence: 95%